INVESTIGAÇÃO DO ESCOAMENTO ATMOSFÉRICO TURBULENTO MODIFICADO POR BARREIRAS POROSAS ARTIFICIAIS E NATURAIS APLICADAS NO CONTROLE DA EROSÃO EÓLICA DE MATERIAIS GRANULADOS - Stocco, Jamily Faé (2021)
The emission of particulate matter and its transport into the atmosphere result in increased concentrations of particles in the atmosphere, causing degradation of air quality and potential generation of risks to human health. The presence of wind barriers around industrial yards of granular materials storage piles is an important method of controlling these fugitive emissions by reducing the near surface wind velocity. Such importance in erosion control motivated the present work, which aims to study turbulent atmospheric flow in the presence of natural and artificial barriers, in order to analyze its influence in reducing the flow velocity and the shelter region due to its presence. Numerical simulations of atmospheric flow through wind barriers were performed using different mathematical modeling setup, in addition to different RANS turbulence models. The results were compared to data from wind tunnel experiments found in the literature to validate the numerical simulations. The sensitivity of the velocity field in relation to the morphological parameters of plant barriers and the porosity of artificial barriers was investigated. The models showed better flow prediction in the inner region of the barrier, and had less precision in predicting the wake results for all scenarios (underestimation of the dimensionless coefficient of velocity reduction). The behavior of the RANS turbulence models was very similar with differences of around 12% for medium and high densities and 34% for low density of trees in the barrier. The use of the vertical profile of the inertial resistance coefficient for the natural barrier improved the flow prediction within the tree barrier, influenced the formation of the shelter region and the friction velocity in the downstream region. Additionally, the porosity parameter of the artificial barrier played an important role in reducing the friction speed for these cases. The increase in porosity led to a milder reduction in the friction velocity in the protection region downstream of the barrier, which was 32% lower when the porosity increased to 60%, but increased the protection area due to the barrier. With the present work it was possible to understand in detail the flow modified by porous barriers to attenuate the wind velocity and to identify best practices of mathematical modeling of porous barriers with a view to application in complete studies involving the erosion of granular materials storage piles and roads in industrial yards.